Blood Lead Levels and Health Problems of Lead Acid Battery Workers in Bangladesh - Sk. Akhtar Ahmad; Manzurul Haque Khan; Salamat Khandker; A. F. M. Sarwar; Nahid Yasmin; M. H. Faruquee; Rabeya Yasmin (The Scientific World Journal)
Introduction. Use of lead acid battery (LAB) in Bangladesh has risen with sharp rise of motor vehicles. As result, manufacture of LAB is increasing. Most of the lead used by these industries comes from recycling of LAB. Workers in LAB industry are at risk of exposure lead and thus development of lead toxicity. Objective. The objective of this study was to measure the blood lead concentration and to assess the magnitude of health problems attributable to lead toxicity among the LAB manufacturing workers. Methods. A cross-sectional study was conducted among the workers of LAB manufacturing industries located in Dhaka city. Result. Mean blood lead level (BLL) among the workers was found to be high. They were found to be suffering from a number of illnesses attributable to lead toxicity. The common illnesses were frequent headache, numbness of the limbs, colic pain, nausea, tremor, and lead line on the gum. High BLL was also found to be related to hypertension and anemia of the workers. Conclusion. High BLL and illnesses attributable to lead toxicity were prevalent amongst workers of the LAB manufacturing industries, and this requires attention especially in terms of occupational hygiene and safety.